Ikhtiar Kontekstualisasi Konstruksi Islam Nusantara - Muhammad Madarik; Hairul Puadi (LP3M IAI Al-Qolam Malang, 2022)
Contextualization is an indisputable fact that can be proven by the existence of religion in each historical period through a dialogical phenomenon between religion and the environment in which religion exists. In fact, the dialogue between religion and the environment sharpens its function and clarifies the significance of its presence among the people, so that religion is truly believed to be the solution to every problem and problem of the general public because religion is brought in a flexible form. Through the two starting points of the above approaches (two anchor approaches), they break what they are touting about assumptions without being based on argumentative evidence.